Low agreement among patients and clinicians about urgency and safety to wait for assessment in primary care after hours medical care: results of cross-sectional matched surveys - Katelyn Barnes; Caitlin Arpel; Kirsty Douglas (BMC, 2023)
Abstract Background Discordance between patient and clinician perceived urgency may drive "inappropriate" presentations to after-hours medical services. This paper investigates the level of agreement between patient and clinicians' perceptions of urgency and safety to wait for an assessment at after-hours primary care services in the ACT. Methods Cross-sectional survey voluntarily completed by patients and then clinicians at after-hours medical services in May/June, 2019. Agreement between patients and clinicians is measured by Fleiss kappa. Agreement is presented overall, within specific categories of urgency and safety to wait, and by after-hours service type. Results 888 matched records were available from the dataset. Overall inter-observer agreement between patients and clinicians on the urgency of presentations was slight (Fleiss kappa = 0.166; 95% CI 0.117-0.215, p < 0.001). Agreement within specific ratings of urgency ranged from very poor to fair. Overall inter-rater agreement on how long it would be safe to wait for assessment was fair (Fleiss kappa = 0.209; 95% CI 0.165-0.253, p < 0.001). Agreement within specific ratings ranged from poor to fair. By site type, agreement between patients and clinicians on urgency ranged from not significant to fair and agreement for safety to wait ranged from very poor to slight. Agreement on urgency of issue was more often reported among patients attending their usual health service or seeing their usual clinician compared to patients attending an unfamiliar health service or clinician (χ2(1) = 7.283, p = 0.007 and χ2(1) = 16.268, p < 0.001, respectively). Conclusions Low levels of agreement between patients and clinicians on perceived urgency and safety to wait for issues to be assessed indicate potential inefficiency in primary care use after-hours. Agreement on urgency of issues was more common among patients attending a familiar health service or familiar clinician. Improving health literacy, particularly health system literacy, and supporting continuity of care may help to support patients to engage with the most appropriate level of care at the most appropriate time.